It Is Indeed for the Protocol: ”Hadrashah” by Haim Hazaz as a Protocol Text - Wosner, Michal (MiKAN, 2008)
This paper focuses on a hitherto undefined textual genre — protocol texts. The genre is based on the extra-literary model of protocols (in the sense of minutes or records) with it own specific distinguishing characteristics from other genres. I argue that protocol texts place the reader in a quasi-judicial position toward the text, calling for specific reading strategies enabling the reader to fulfill his / her judicial role. The argument is demonstrated by a close reading of the short story "Hadrashah" by Haim Hazaz, written in the protocol genre. The story is analyzed by the protocol reading strategy and interpreted as the vain attempt by the individual to raise a puny personal problem at a time devoted to great historic moves.